CircRNA_0005075 suppresses carcinogenesis via regulating miR‐431/p53/epithelial‐mesenchymal transition axis in gastric cancer. (4th March 2020) - Wu, Jiaming; Chen, Zhiheng; Song, Yihuan; Zhu, Yi; Dou, Guangjian; Shen, Xuning; Zhou, Yuan; Jiang, Honggang; Li, Jin; Peng, Yuping
Abstract : This study was aimed to explore the expression and biological function of circRNA_0005075 in gastric cancer (GC) progression and its underlying mechanism. First, the expression level of circRNA_0005075 and microRNA‐431 (miR‐431) in GC tissues were detected with the quantitative real‐time polymerase chain reaction. In addition, after down‐regulated the circRNA_0005075 expression by plasmid transfection in GC cells, the Cell Counting Kit‐8 (CCK‐8), EDU, transwell assay were conducted to evaluate the function of circRNA_0005075 or miR‐431 on cell proliferation, metastasis in vitro. Moreover, p53 and Epithelial‐mesenchymal transition (EMT) pathway related proteins were also measured with western blotting. Then, our data revealed that CircRNA_0005075 was found to be significantly up‐regulated in GC tissues as well as GC cell lines, and the GC patients with higher CircRNA_0005075 expression were more likely to have poor outcomes. Down‐regulation of CircRNA_0005075 could significantly suppress the GC cell proliferation and cell metastasis ability, while the addition of miR‐431 inhibitors could counteract this effect. Importantly, we discovered that the silencing of circRNA_0005075 could weaken the micro‐RNA sponge function for miR‐431, and then upregulate the expression of p53 and forbid the EMT signalling pathway, and finally suppress the tumourigenesis of GC. To sum up, CircRNA_0005075 could inhibit cell growth and metastasis of GC through regulating the miR‐431/p53/EMT axis. Significance of the study: The research clearly elucidated the potential role and relative regulatory mechanism of circRNA_0005075 in gastric cancer (GC) progression. Briefly, circRNA_0005075 could directly inhibit the expression level of miR‐431, then regulate the p53/Epithelial‐mesenchymal transition axis, and finally inhibit cell growth and metastasis in GC. Consequently, circRNA_0005075 might act as an oncogene in the GC procession, which provides a promising way for the treatment of GC.